The sisters of Sea View - Klassen, Julie, 1964- (Klassen, Julie, 1964- On Devonshire shores, 2022)
"When their father's death leaves them impoverished, the Summers sisters open their home to guests to provide for their ailing mother. But instead of the elderly invalids they expect, they find themselves hosting eligible gentlemen. Sarah must confront her growing attraction to a mysterious widower, and Viola learns to heal her deep-hidden scars"--